A Review of Working and Nonworking Women's Attitudes on Fashion Clothing (Journal of Advances and Scholarly Researches in Allied Education, 2020)
This review explores the complex link between clothes, culture, and personal identity by examining the views of working and non-working women towards fashion apparel. The research explores how clothing has changed historically, from its rudimentary beginnings to its current position as an essential component of daily existence. It looks at how societal, psychological, and economical variables affect what people wear and how that, in turn, reflects on their values and personality. The study also looks at how women's views towards fashion are influenced by their work status, going into how having more money may have an impact on what women choose to wear and how they express themselves in general. This study seeks to shed light on the complex interactions that exist between personality, fashion, and socioeconomic position in order to better understand the diverse ways that women relate to clothes in both professional and informal settings.